2011
DOI: 10.1017/s1041610211002225
|View full text |Cite
|
Sign up to set email alerts
|

A long-term care center interdisciplinary education program for antipsychotic use in dementia: program update five years later

Abstract: Despite the low prevalence (17.2%) of AP users at the beginning of the current study compared to that observed five years prior (30.5%), it is still possible to further decrease the proportion of users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Our results regarding prevalence of AP use are consistent with previous studies among individuals with dementia [2427], whereas other authors reported much higher rates of AP use [12, 2832]. The settings of the present analysis may explain some of the observed discrepancies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results regarding prevalence of AP use are consistent with previous studies among individuals with dementia [2427], whereas other authors reported much higher rates of AP use [12, 2832]. The settings of the present analysis may explain some of the observed discrepancies.…”
Section: Discussionsupporting
confidence: 90%
“…If the efficacy of safety warnings issued by health authorities in reducing AP use is controversial, some targeted educational interventions aimed at health care professionals and at a local level have shown a relative efficacy if provided regularly [14, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 studies were included (table 2). 23–35 These 13 studies were published between 2002 and 2016 (six studies within the last decade). Studies were conducted in the USA (6),23–28 Australia (2),29 30 Canada (2)31 32 and the Netherlands (3) 33–35…”
Section: Resultsmentioning
confidence: 99%
“…Studies’ methodologies varied across chronic diseases, study design and duration, sample selection, number and type of CCM10 components used in the intervention(s), and intervention activities (table 1). The majority of studies (76.9%) focused on management of dementia 23 24 26 27 29–31 33–35. Two studies25 32 focused on managing diabetes mellitus and one study28 evaluated the management of heart failure.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review identified 22 interventions that have been developed to address inappropriate antipsychotic use in nursing homes [ 4 ]. This review noted that medication audit initiatives typically collect data by visiting the home and copying resident charts [ 4 , 10 , 11 ] using cohorts already detailed by other studies [ 12 , 13 ] or by accessing electronic pharmacy records [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%